Hints for the busy housewife (London : Health & Cleanliness Council)
1939-05 1939 1930s 50 pages : illustrations HINTS FOR THE BUSY HOUSEWIFE (moistened) with the dry powder. Bring to the boil and boil for a few minutes. Lift out of the wash-boiler and rinse thoroughly. Handkerchiefs before washing and boiling should be placed for some time in half a bucket of cold water with a handful of common salt thrown in. This hardens any mucus adhering to the fabric and enables it to be rubbed off easily. Wash them with a little disinfectant in the water, especially after colds or influenza, and keep them apart from other articles until cleansed for the copper. Baby's Napkins should first be soaked well, then washed with a good soap and without soda. Rinse in several waters, boil, wring tightly and hang out to dry. Stains on Tableclothes. — A fresh stain of tea, coffee, or cocoa can often be quickly removed by pouring boiling water and a little soda through. Allow an old stain to soak in glycerine for some time. After the stain is removed wash the tablecloth in the usual way. Boiling and outdoor drying will finally bleach it. Ink Stains. — Ink, if fresh, is removable by placing the stained part in buttermilk or in milk. Otherwise moisten with salt and lemon juice, lay in the sun, and wash afterwards in soap-suds. If salts of lemon, which is poison, is used for removing ink or ironmould (½ teaspoon-ful to ¼ pint boiling water), care must be taken to rinse the part in cold water immediately, otherwise the fabric will be weakened. Mildew, which is caused by putting clothes away damp, can be removed from white cloth by soaking the stain for several hours in hydrogen Page Twenty-five 177/5/8/1